If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9y = 2 Solving 4x + 9y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 4x + 9y + -9y = 2 + -9y Combine like terms: 9y + -9y = 0 4x + 0 = 2 + -9y 4x = 2 + -9y Divide each side by '4'. x = 0.5 + -2.25y Simplifying x = 0.5 + -2.25y
| 72/3*4-2+10=-6 | | 20b^2-245= | | 14-y=1 | | 0.20x+0.45(50)=36.5 | | h+|-8|=15 | | 2n/-5=4/6 | | 8x+7=-3+5x+19 | | 2(d+7)-(3d+5)=2d+(4d-9+3d)-(d+3) | | 1.50m+5=15.50 | | -2/3r+2r=6/5r+8/5 | | 4(3r+2)-2r=-10 | | 0.50f+5=11.50 | | -8(r+5)=-18-8r | | 3=8x+4 | | -6(2+7k)=-12+4k | | 2(n-2)=2+4n | | 4(3n-2)=64 | | -16+3y=4 | | -2=-2-3(4-2k) | | 10k+3=8k+27 | | 72=6(-2+7x) | | 55=18+0.004x | | 32=4(1-7k) | | 2a+4a-13=47 | | 4x-6=3x+1-x-7 | | -5(3x+4)=2(9-6x) | | -36=6X-12Y | | 384628x+298473=2937474 | | 6(5-7n)=72 | | -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x |